Comparing the effectiveness of intranasal Midazolam and intravenous Lorazepam for the treatment of acute seizures in children - Bhadran, Kingini; Roy, Dhanya; Mathai, Isac (Indian Journal of Child Health, 2018)
Objective: The objective of this study was to compare the safety and efficacy of intranasal midazolam with intravenous lorazepam in acute seizures in children. Methods: Children aged 6 months–12 years with active tonic/clonic/tonic-clonic seizures coming to the pediatric emergency department were enrolled in the study after getting informed consent. Groups were randomly distributed (Group 1: Intranasal midazolam; Group 2: IV lorazepam) and the sample size was 80 (40 in each group). Under clinical and pulse oximetry monitoring, aqueous midazolam 0.2 mg/kg was administered intranasally through automated aqueous intranasal spray(Midacip 0.5mg per puff) in lying down or in 45° propped up position to Group 1, while injectable lorazepam 0.1 mg/kg was administered intravenously slow (to a maximum of 4 mg) to Group 2. Results: Both the groups were found to be comparable in baseline characteristics. Mean time to administer the drug after arrival to the doctor in intranasal midazolam and IV lorazepam was 3.65 (standard deviation [SD] 1.167) min and 7.93 (SD 3.23) min, respectively (p=0.0001). Intranasal midazolam group had significant control of seizures in